Performance comparison of sensible and latent heat-based thermal storage system during discharging – an experimental study. Issue 1 (2nd January 2022) - Suresh, C.; Saini, R.P.
ABSTRACT: Thermal energy storage system has significant influence on energy conservation. Based on the literature review, it is identified that very few studies have been reported on performance assessment of latent and sensible thermal energy storage systems. This study presents an experimental study on latent and sensible thermal energy storage systems to investigate their performance during discharging cycle. Results have shown that the latent heat storage system has improvement of about 104% in discharging time and 4.1 times more energy is recovered as compared to the sensible heat storage system. It is recommended on the basis of obtained results to operate the systems at lower mass flow rate during discharging.